Trends in the swine industry: productivity measures - Kevin C Dhuyvetter; J L Parcell (Kansas Agricultural Experiment Station Research Reports, 1997)
Productivity has been trending up in the swine industry over the last 15 years. Much of the increased productivity is due to increased pigs/litter and increased market weights. The efficiency of the breeding herd (litters/sow/year) has been trending up in the U.S. but has remained relatively constant in Kansas.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; Industry trends; Productivity; Breeding herd efficiency